2011
DOI: 10.1080/21567069.2011.586677
|View full text |Cite
|
Sign up to set email alerts
|

Using technology to encourage student engagement with feedback: a literature review

Abstract: This article presents a review of the literature over the past 10 years into the use of technological interventions that tutors might use to encourage students to engage with and action the feedback that they receive on their assessment tasks. The authors hypothesise that technology has the potential to enhance student engagement with feedback. During the literature review, a particular emphasis was placed on investigating how students might better use feedback when it is published online. This includes where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 46 publications
2
49
0
1
Order By: Relevance
“…Perhaps this is at the root of the widespread student dissatisfaction with assessment feedback in higher education. Technological advances in delivery of feedback are educationally neutral (Hepplestone et al 2011). It is only the relationships between the student and the instructor which can enhance learning.…”
Section: Separation Of Feedback From Marksmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps this is at the root of the widespread student dissatisfaction with assessment feedback in higher education. Technological advances in delivery of feedback are educationally neutral (Hepplestone et al 2011). It is only the relationships between the student and the instructor which can enhance learning.…”
Section: Separation Of Feedback From Marksmentioning
confidence: 99%
“…With substantial investment by Higher Education Institutions (HEIs) in learning technologies such as Virtual Learning Environments (VLEs), the last decade has seen technology increasingly used to mediate between students and teaching staff (Hepplestone et al 2011). While institutions need to recoup investment and manage growing student numbers in a time of financial stringency, it is valid to ask whether technology is the answer or merely generates another problem with feedback on student work, increasing remoteness from teaching staff.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas many papers reported using technology as a tool to support self-appraisal, the primary intended purpose of technology-based interventions was to enable pre-HE and HE learners to become more motivated to engage with feedback (see Hepplestone, Holden, Irwin, Parkin, & Thorpe, 2011, for a review from HE). Perhaps for this reason, much of the primary emphasis among these papers was on learners' satisfaction with-rather than their use of-their feedback.…”
Section: Manner Of Feedback Deliverymentioning
confidence: 99%
“…A literature review on the use of technology in feedback by Hepplestone, Holden, Irwin, Parkin, and Thorpe (2011) made no reference to video-based feedback. However, in a similar review of technologies for learner-centred feedback, Costello and Crane (2010) identified video as having some benefits, but their conclusion is based on two sources, only one of which was based on empirical evidence (Parton, Crain-Dorough, & Hancock, 2010), while the other (Denton, Madden, Roberts, & Rowe, 2008) is itself making a passing reference to a much older article from 1997 (Hase & Saenger, 1997).…”
Section: Video-based Assessment Feedbackmentioning
confidence: 99%